Analysis Of Topic Movement & Conversation Membership On Twitter Using K-Means Clustering - Sediyono, Agung; Valentino Hutagalung, Josua; Solihah, Binti (Penerbitan Universitas Trisakti, 2024)
Humans are born to socialize with each other. Social media is one of the media to be able to socialize with each other. Twitter is one of the social media that contains hundreds of millions of tweets where the tweet contains news, products that are currently popular, even about the daily life of users who can change. Social Context Analysis is a tool to analyze social changes and individual needs in society from time to time. In this study, the author uses the K-means Clustering method to group topics on Twitter. In its implementation, this research is expected to be able to see the occurrence of topic movements and membership movements on Twitter topics.